The Effect of Storytelling through Book Creator to Improve Students’ Reading Comprehension - Tuminah, Tuminah; Kurniawan, Donie Fadjar; Faridha, Noor (Edulitics (Education, Literature, and Linguistics) Journal, 2022)
This research proposed to find out whether local storytelling through book-creator was effective to enhance students’ reading comprehension. The quasi-experimental design was applied to English department students of STKIP Pamane Talino as the population. Among the population, 60 students were selected as the research sample through purposive sampling that further divided into the experimental group taught using book creator and the control group taught using the drill method. The data were obtained through pre and post-test in the form of 5 essay questions. Between the tests, two treatments were given to the experimental group. After the second treatment, both groups were given a posttest. The data obtained were further analyzed using a t-test through SPSS. The data analysis showed that based on the independent sample test that the significant value was 10,095 which is higher than than the critical score 1.8731 where the gain score of experimental group (0,8) was higher than that of the control group (0.3). Therefore, the conclusion that can be drawn from the research result was that using a book creator in teaching reading is effective. Consequently, teachers are recommended to use book-creator as local storytelling to enhance students' reading comprehension, especially for English department students in STKIP Pamane Talino.